2019
DOI: 10.1017/s0305741019000067
|View full text |Cite
|
Sign up to set email alerts
|

Two Steps Forward, One Step Back: Chinese State Reactions to Labour Unrest

Abstract: What impact is the current rise in workplace conflict having on governance in China? This article argues that, over time, protests are driving the state in two directions at once: towards greater repression and greater responsiveness. Using an original dataset of strikes, protests and riots by Chinese workers between 2003 and 2012, along with government budgetary and judicial statistics, the article demonstrates that significant, positive correlations exist at the provincial level between increased unrest on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…This development might have created optimism over raising workers' consciousness and the potential of labour agency to pressure state and management (Pun and Lu 2009;Chan 2010: Froissart 2018. However, the Chinese labour movement has experienced "one step back," in the words of Elfstrom (2019), since President Xi Jinping took to power and the party-state adopted a hard-line policy over civil society (Howell and Pringle 2019). Meanwhile, the Chinese economy has slowed down since 2012, with many factories closing and relocating to Southeast Asia.…”
Section: Labour Agency In a Changing Labour Marketmentioning
confidence: 99%
“…This development might have created optimism over raising workers' consciousness and the potential of labour agency to pressure state and management (Pun and Lu 2009;Chan 2010: Froissart 2018. However, the Chinese labour movement has experienced "one step back," in the words of Elfstrom (2019), since President Xi Jinping took to power and the party-state adopted a hard-line policy over civil society (Howell and Pringle 2019). Meanwhile, the Chinese economy has slowed down since 2012, with many factories closing and relocating to Southeast Asia.…”
Section: Labour Agency In a Changing Labour Marketmentioning
confidence: 99%
“…The finding from this chart resonates with those of other studies that have found that the Xi administration has adopted different approaches from the Hu–Wen administration in responding to workers’ collective actions. See, e.g., Fu and Distelhorst 2017; Elfstrom 2019.…”
Section: How Do Local Governments React To Workers’ Collective Actions?mentioning
confidence: 99%
“…The seeming advances made through the endowment of a growing array of individual rights for workers are, however, undermined by the continued absence of collective rights, namely the right to organise and strike (Chen 2007). In addition to this legal fix of 'rule by law', the Party-state also uses its 'responsive and repressive capacities'-welfare concessions and some experimentation with democratic elections to trade unions (such as in Guangdong), on the one hand, and the use of public security apparatus and agencies to quell protests, on the other-to meet labour unrest (Elfstrom 2019b).…”
Section: Labour and The Communist Party Of China Before The 1978 Reformsmentioning
confidence: 99%